What do household surveys suggest about the top 1% incomes and inequality in OECD countries? - Ruiz, Nicolas (OECD Publishing, 2016)
Standard income inequality figures, based on official household survey statistics covering most of the population, report a steady rise of inequality across a majority of advanced countries. The usefulness of these data sources in providing a timely and internationally comparable picture of inequality is undisputed, but one well-known limitation is their under-reporting of top incomes. This matters insofar as separate data sources devoted specifically to top incomes evolution report substantially faster inequality growth in recent years compared to conventional statistics. This paper proposes a methodology to adjust household survey data for the under-reporting of top incomes. More specifically, the analysis delivers a set of top incomes-adjusted income distribution series that bring together the bottom 99% and the top 1%. Unsurprisingly, the results point to a significant increase of the level of inequality measured by standard statistics based on official figures: the Gini coefficient adjusted for top incomes was in 2011 on average 6 percentage points higher, moving from 0.31 to 0.37 for the average OECD country; similarly, the gap between the mean income of the richest and the poorest 10% rises from 10 to 15 as a result from the adjustment. Inequality trends are also significantly altered, albeit in ways that differ across countries
Keywords: Economics